1998
DOI: 10.1017/s0956792598003507
|View full text |Cite
|
Sign up to set email alerts
|

Artificial boundary conditions of absolute transparency for two- and three-dimensional external time-dependent scattering problems

Abstract: For an external problem in IRd (d=2, 3) such that the unknown function satisfies the wave equation outside a finite domain, we generate artificial boundary conditions transparent to outgoing waves. These conditions permit an equivalent replacement of the original external problem by the problem inside the artificial boundary which is a circle (d=2) or a sphere (d=3): The questions of numerical implementation of the artificial conditions (that are non-local in both space and time) are considered. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 5 publications
0
48
0
1
Order By: Relevance
“…That is, one can avoid the storage of the time history evident in (2.33)-(2.34). This fact was independently exploited by Sofronov [63,64] and Grote and Keller [28,29,30] to derive and implement accurate temporally local conditions. (See also [31] for applications to multiple scattering.)…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, one can avoid the storage of the time history evident in (2.33)-(2.34). This fact was independently exploited by Sofronov [63,64] and Grote and Keller [28,29,30] to derive and implement accurate temporally local conditions. (See also [31] for applications to multiple scattering.)…”
Section: 22mentioning
confidence: 99%
“…For the case of a spherical boundary, we have already observed that the kernels are exactly equal to sums of exponentials (2.35). This leads to an algorithm which is mathematically equivalent to the one proposed by Sofronov [63,64] and Grote-Keller [28,29,30]:…”
Section: 4mentioning
confidence: 99%
“…This successful method is then applied to Maxwell's equations [30] and elastic waves [31]. Another form of the exact nonreflecting boundary conditions for the scalar wave equation was obtained by Sofronov [54] independently. A systematic approach to the computation of exact conditions has been studied [1].…”
Section: Introductionmentioning
confidence: 99%
“…They extended this NRBC for the case of elastic waves in Reference [13]. Sofronov [14,15] has independently published a similar scheme in the Russian literature. Hagstrom and Hariharan [16,17] constructed high-order NRBCs for the two-and three-dimensional time-dependent wave equations based on the analytic series representation for the outgoing solutions of these equations.…”
Section: Introductionmentioning
confidence: 99%